MENINGKATKAN PRESTASI BELAJAR IPA MELALUI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS (TGT) PADA MATERI BENDA DAN SIFATNYA - Ma'as Shobirin; Siti Rochmana (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2017)
This study aims to describe the implementation of learning model of Teams Games Tournaments (TGT) and measure an increaseing in the achievements of science through a model of TGT on the students of class V MI Gebanganom Semarang Timur. The research used a classroom action reasearchs. This includes several methods PTK stages, namely planning, action, the observation and reflection. The process of the study was conducted as much as 2 cycle and 1 pre- cycle. The indicator of the success of this research is increasing the achievements science. The results of research based on the show that an increase in the learning achievements was significant. It is known of the data activities cycle I being active learn students of 73,5 %, while cycle II on the rise of 89,28 %. This is evident from the percentage of completeness learned in classical, namely of the data early or pre- cycle of 47,05 %, on the cycle I of 76,47 %, and in the cycle II on the rise of 94,12 %. Thus, the implementation of learning model TGT was very effective to improve the student’s achievement.